Nuclear Science and Safety in Europe - Cechák, Tomas; Jenkovszky, László; Karpenko, Iurii (Nato Security through Science Series B, Physics and Biophysics, 2006)
Recent results on the nature of low-, intermediate- and high-energy nuclear forces as well as on the internal structure of nucleons and atomic nuclei are presented. Prospects to find a new state of the nuclear matter at extreme conditions that existed in the early Universe and the utilisation of the nuclear energy are discussed.